Bio-evaluation and molecular modeling studies of ARG-TRP-ARG-based peptides as antimicrobial agents - Akintayo, Emmanuel T.; Stella, Olaoye; Akintelu, Sunday Adewale; Oyebamiji, Abel Kolawole (Edelweiss Applied Science and Technology, 2025)
The battle against bacterial infections in both young and elderly populations continues to be a focus for researchers worldwide. This issue has led to the discovery of the most effective antibacterial ARG-TRP-ARG-based peptides through density functional theory and molecular modeling analysis. In this research, the inhibitory effectiveness of an ARG-TRP-ARG-based peptide was evaluated using in silico methods. The optimization was carried out with density functional theory, while molecular modeling studies were performed using induced-fit docking and molecular dynamics simulations. Compounds 3 and 4 showed promising responses regarding their HOMO energy, with compound 3 displaying a stronger propensity for favorable reactions in terms of energy gap. It was noted that compound 10, which possessed the lowest LUMO energy value, had the highest ability to accept electrons from nearby compounds. Additionally, when testing the compounds against thymidylate kinase from gram-positive bacteria (4HLC) and gyrase B from Thermus thermophilus (1KIJ), compounds 9 and 5 demonstrated the most significant inhibition of the targeted receptors. Molecular dynamics simulations confirmed the effectiveness of the lead compounds as predicted by the docking approach. Furthermore, the binding affinities were predicted from the calculated descriptors using Python (v3.11), and the results were presented accordingly.